1996
DOI: 10.2466/pms.1996.83.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Scores on the Profile of Mood States following a Single Bout of Physical Activity: Heart Rate and Changes in Affect

Abstract: 28 college age students participating in a weight lifting class exhibited significant decreases in negative affect and increases in positive affect. Changes in affect were correlated with average exercise heart rates. Higher heart rates were correlated with reductions in negative affect and increases in positive affect. Correlations of .37 and .40 suggest that, in accordance with earlier studies, exercise intensity may be indirectly related to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
2
8
0
5
Order By: Relevance
“…17 Bodin and Martinsen 18 found similar changes in positive and negative affect following exercise in a group of depressed individuals experiencing increased self-efficacy but not in those who did not experience increased selfefficacy. McGowan, Talton and Thompson 19 found similar changes after a weight lifting class in college students. Raedeke 20 also found these changes in affect after an exercise session and further found that exercise enjoyment moderated changes in positive affect but was unrelated to changes in negative affect.…”
Section: Introductionsupporting
confidence: 50%
“…17 Bodin and Martinsen 18 found similar changes in positive and negative affect following exercise in a group of depressed individuals experiencing increased self-efficacy but not in those who did not experience increased selfefficacy. McGowan, Talton and Thompson 19 found similar changes after a weight lifting class in college students. Raedeke 20 also found these changes in affect after an exercise session and further found that exercise enjoyment moderated changes in positive affect but was unrelated to changes in negative affect.…”
Section: Introductionsupporting
confidence: 50%
“…So, while exercising many systems of the body as cognitive, skeletal-muscular or cardiovascular, interact in a somewhat general or holistic manner together with positive and negative moods (Thayer et al, 1994). Moreover, McGowan et al (1996) showed that changes in affect were correlated with average HR. Higher HR was associated with reductions in negative affect and increases in positive affect.…”
Section: Discussionmentioning
confidence: 96%
“…[7,17] However, no-exercise control conditions have not always been used. [3] In other studies, improvements in energy and fatigue have not been observed [18] or were inconsistent across time. [19,20] Acute exercise may have larger effects on measures of energy than fatigue, [7] but biomedical researchers often focus on fatigue and neglect or de-emphasize energy.…”
mentioning
confidence: 98%